Design of Stand-alone Solar-Wind-Hydro Based Hybrid Power System: Case of Rural Village in Malawi - Sylvester William Chisale; Zaki Sari (Advanced Aspects of Engineering Research Vol. 4, 2021)
Malawi has current electrification rate of less than 10% for a population of 18 million connected to the grid. The electricity generation company in Malawi (EGENCO) is greatly affected by low water levels making it difficult to satisfy the existing demand of electricity. This makes it difficult for Malawi to extend its National electricity grid. Thus, the aim of the study is to design stand-alone hybrid renewable energy system which is economically and technically feasible with focus on hydropower, wind, solar and battery bank within Dwangwa area. The study area is estimated to have 420 households, commercial and public service load with primary load demand of 5,556.31 kWh/day and peak load of 302.93 kW. River discharge data were collected from ministry of irrigation and water development while solar and wind data were collected from NASA. HOMER modeling tool was used to design a stand-alone system. From simulation results, the best design flow for Dwangwa river is 159 L/s at elevation of 100 metres and the best hybrid system combination was hydropower-wind-solar-battery and converter. The whole hybrid system initial capital cost was 2,662,638 while Net present cost (NPC) and levelized cost of energy (LCOE) were 3,597,197 and 0.134/kWh respectively. However, the cost of electricity in Malawi on the grid is K88.02/kWh (0.11/kWh) which makes the system expensive. Therefore, the study has shown that the hybrid system is not economically viable. However, Government intervention can help to make the system monetarily acceptable and viable.